GammaTile® brachytherapy in the treatment of recurrent glioblastomas. Issue 1 (27th December 2021) - Gessler, Dominic J; Neil, Elizabeth C; Shah, Rena; Levine, Joseph; Shanks, James; Wilke, Christopher; Reynolds, Margaret; Zhang, Shunqing; Özütemiz, Can; Gencturk, Mehmet; Folkertsma, Mark; Bell, W Robert; et al.
Abstract: Background: GammaTile® (GT) is a recent U.S. Food and Drug Administration (FDA) cleared brachytherapy platform. Here, we report clinical outcomes for recurrent glioblastoma patients after GT treatment following maximal safe resection. Methods: We prospectively followed twenty-two consecutive Isocitrate Dehydrogenase (IDH) wild-type glioblastoma patients (6 O 6 -Methylguanine-DNA methyltransferase methylated (MGMTm); sixteen MGMT unmethylated (MGMTu)) who underwent maximal safe resection of recurrent tumor followed by GT placement. Results: The cohort consisted of 14 second and eight third recurrences. In terms of procedural safety, there was one 30-day re-admission (4.5%) for an incisional cerebrospinal fluid leak, which resolved with lumbar drainage. No other wound complications were observed. Six patients (27.2%) declined in Karnofsky Performance Score (KPS) after surgery due to worsening existing deficits. One patient suffered a new-onset seizure postsurgery (4.5%). There was one (4.5%) 30-day mortality from intracranial hemorrhage secondary to heparinization for an ischemic limb. The mean follow-up was 733 days (range 279–1775) from the time of initial diagnosis. Six-month local control (LC6 ) and twelve-month local control (LC12 ) were 86 and 81%, respectively. Median progression-free survival (PFS) was comparable for MGMTu and MGMTm patients (~8.0 months). Median overall survival (OS) was 20.0 months for the MGMTu patients and 37.4 months for MGMTm patients. These outcomes compared favorably to data in the published literature and an independent glioblastoma cohort of comparable patients without GT treatment. Conclusions: This clinical experience supports GT brachytherapy as a treatment option in a multi-modality treatment strategy for recurrent glioblastomas.